2022
DOI: 10.3390/ijerph19020686
|View full text |Cite
|
Sign up to set email alerts
|

Preference of Older Adults for Flexibility in Service and Providers in Community-Based Social Care: A Discrete Choice Experiment

Abstract: Empowerment of control and choice of the service users in health and social care has been incorporated into service provision in various countries. This study aimed to elicit the preference of community-based long-term care (LTC) service users on levels of flexibility in service provision. A discrete choice experiment was performed among older community care service users to measure their preference for attributes of LTC services identified from a prior qualitative study. Each participant was asked to make cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Clients valued a highly skilled workforce who received adequate training to meet their individual needs (Anderson et al, 2006 ; Royal Commission, 2020 ; Spoorenberg et al, 2015 ). The relationship between a highly skilled workforce and client satisfaction was also evident with clients valuing the use of skilled social work professionals to act as care managers coordinating a clients' care needs (Chesterman et al, 2001 ; Wang et al, 2022 ). Having consistent staff who were well trained was a strong theme throughout the literature that resulted in improved client satisfaction (Byrne et al, 2011 ; Groenewoud et al, 2008 ; McCaffrey et al, 2015 ; Royal Commission, 2020 ; Samuelsson & Wister, 2000 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clients valued a highly skilled workforce who received adequate training to meet their individual needs (Anderson et al, 2006 ; Royal Commission, 2020 ; Spoorenberg et al, 2015 ). The relationship between a highly skilled workforce and client satisfaction was also evident with clients valuing the use of skilled social work professionals to act as care managers coordinating a clients' care needs (Chesterman et al, 2001 ; Wang et al, 2022 ). Having consistent staff who were well trained was a strong theme throughout the literature that resulted in improved client satisfaction (Byrne et al, 2011 ; Groenewoud et al, 2008 ; McCaffrey et al, 2015 ; Royal Commission, 2020 ; Samuelsson & Wister, 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Clients valued a highly skilled workforce who received adequate training to meet their individual needs (Anderson et al, 2006;Royal Commission, 2020;Spoorenberg et al, 2015). The relationship between a highly skilled workforce and client satisfaction was also evident with clients valuing the use of skilled social work professionals to act as care managers coordinating a clients' care needs (Chesterman et al, 2001;Wang et al, 2022).…”
Section: Quality Domain 1: Knowledge Of Staffmentioning
confidence: 99%
“…Regarding flexibility of choice in care services, previous studies in the UK reported that care home residents with fewer cognitive problems were more likely to benefit from individualized care services than residents with greater cognitive disadvantages, as the latter had limited capacities to exercise their choices [ 10 , 36 ], and older persons with ADL impairment in Hong Kong were found to have less preference for flexible services [ 37 ], while communication problem was not found associated with this preference. However, the ability of those with communication problems to exercise flexible choices is threatened by their limited mental capacity [ 38 ], which suggested that there should be personnel and mechanisms in place to assist these residents in optimizing their control and choices over services.…”
Section: Discussionmentioning
confidence: 99%
“…Ten of the eleven papers reference the complexity of decision making [13,15,[24][25][26][27][28][29][30]32]. Factors that complicate decision making in older age are numerous, including time, trade-ofs, information quality, the number of decisions being made, and the number of choice options within those decisions [13,25,26,28].…”
Section: ) Decision Making Is Complex (Which Induces Heuristic Decisi...mentioning
confidence: 99%
“…Another prevalent assumption is that decision-making strategies remain fxed, i.e., that a person will make a decision in the same way when they are 20 as they will when they are 60 [31]. Evidence presented in ten of the articles suggests this is not the case, indicating that age-related changes in decision making are measurable and that the overall efect is a decline in decision quality [13,15,[24][25][26][27][28][30][31][32]. Te reasons for this decline are generally related to cognitive function [13,15,24,28,31,32], including decreases in processing speed [24,31], executive function [24], and working memory.…”
Section: ) Decision Making Is Complex (Which Induces Heuristic Decisi...mentioning
confidence: 99%